Calcification of the stylohyoid ligament and elongated styloid process: a finding during a medical-legal autopsy for sudden death (2015)
Purpose: The relationship between Eagle syndrome and both sudden death andforensic sciences has been rarely described in the literature; then, it is necessary to consider this anatomical-pathological alteration both from a clinical and forensic point of view, since its few symptoms do not allow an early diagnosis, which can lead to death due to certain pre-existing physical conditions such as heart or vascular disease. Topics: Elongation of the styloid process and calcification of the stylohyoid ligament have been reported as a condition that causes pain in the neck and head, known as the Eagle syndrome. Development: The case of a 48-year-old man with underlying heart disease and whose cause of death, after dismissing toxicological causes, was correlated to the findings and an underlying heart disease. Conclusions: Anatomical-pathological changes should be considered when starting autopsies in case of death or any alteration during neck manipulation, such as physical therapies and contact sports, thus creating medical-legal responsibilities.